Pulmonary Hilar Cavernoma - Roxana Ternoveanu; Laurent Médart; Malek Tebache (Journal of the Belgian Society of Radiology)
Teaching point: Description of a new radiological sign named “pulmonary hilar cavernoma” in a case of unilateral total pulmonary vein thrombosis.